Importing, Exporting and Innovation in Developing Countries - Seker, Murat (World Bank, Washington, DC, 2014)
Recent studies have shown that not only exporters but also importers perform better than firms that do not trade. Using a detailed firm level dataset from 43 developing countries, I show that there are persistent differences in evolution of firms when they are grouped according to their trade orientation as: two-way traders (both importing and exporting), only exporters, only importers, and non-traders. Extending the existing models of firm evolution in open economies by incorporating importing decision, I show that: i) globally engaged firms are larger, more productive, and grow faster than non-traders; ii) two-way traders are the fastest growing and most innovative group who are followed by only-exporters; iii) estimating export premium without controlling for import status is likely to overestimate the actual value by capturing the import premium; and iv) R&D investment contributes to growth of traders significantly more than to non-traders. Finally I show the robustness of the findings by providing evidence from the panel data constructed from the original dataset and controlling for variables that are likely to affect firm growth.